Diversity and composition changes of intestinal fungi in patients with chronic kidney disease - XIE Huichao; XIAO Weidong; HAN Ben (陆军军医大学学报)
Objective‍　‍To analyze the diversity and composition changes of gut fungal communities between patients with chronic kidney disease （CKD） and healthy controls. Methods‍　‍A total of 8 CKD patients admitted in Department of Nephrology of our hospital， and another 5 age- and gender-matched healthy individuals were recruited in this study. Fresh fecal samples were collected from the CKD patients and healthy controls. ITS DNA sequencing was employed to determine the composition of intestinal fungi， and then bioinformatics analysis was applied to compare the differences in fungal community diversity， structure， and function between the 2 groups. Results‍　‍There were no statistical differences between the 2 groups in terms of age， gender composition， BMI， and so forth. The results of Alpha diversity assessment showed statistical differences were observed in Simpson index and Shannon index in the intestinal fungi between the 2 groups （P<0.01）. So was in the Beta diversity between them （P<0.01）. The relative abundance of Candida was increased significantly （P<0.01）， while those of Cladosporium and Penicillium were decreased in the CKD group （P<0.05）. LEfSe analysis revealed that Candida was significantly enriched in CKD patients， whereas Cladosporium and Penicillium were significantly lower in abundance when compared to the healthy control group. Conclusion‍　‍The composition of intestinal fungi in CKD patients is different from that in healthy individuals， exhibiting characteristic changes. Dysfunction of gut fungal flora may promote the progression of CKD. Regulating gut fungi and restoring gut microbiota homeostasis may become a new strategy for CKD treatment.